Implementation of 9P Marketing Mix Strategy in Order to Increase Sales Volume in Abdul Ghoffar Rejotangan Tulungagung's Koi Fish Farming Business - Irkha Fitriana Jumari; Sri Eka Astutiningsih (Ilomata International Journal of Management, 2022)
The marketing mix consists of all the things a company can do to find out the demand for its products. This research was aimed to analyze the application of the 9P marketing mix strategy in increasing sales volume as an effort to maximize profits in the Abdul Ghoffar Rejotangan Tulungagung’s Koi Fish Farming Business. This research used descriptive research methods and STP with a qualitative approach. Sources of data in this research were primary and secondary data. Data collection techniques used observation, interviews, questionnaires, and documentation. The research was carried out with 5 informants, they were business owners, employees, consumers 1, consumers 2, and competitors. The results showed that the 9P marketing mix strategy at the Abdul Ghoffar Rejotangan Tulungagung’s Koi Fish Farming Business was carried out in various ways. First, the various products produced with 11 kinds of fish, good quality products concerning the size of the koi fish, and innovative products. Second, the price offered was affordable according to the target market. Third, marketing and delivery locations were strategic and easy to reach. Fourth, various promotions so prospective consumers could easily find products. Fifth, good quality business locations by classifying fish according to conditions. Sixth, conducted training for employees to produce good service to consumers. Seventh, an effective delivery process by choosing the right distributor. Eighth, did safe packaging. Ninth, used an easy payment method. This research concluded that the implementation of the 9P marketing mix strategy can have an impact on increasing sales volume in Abdul Ghoffar Rejotangan Tulungagung’s Koi Fish Farming Business.